An analysis of multimodal resources in environmental protection posters - Dallyono, Ruswan; Sukyadi, Didi (Indonesian Journal of Applied Linguistics, 2019)
Exposure of environmental issues is essential to prevent mass environmental destructions; therefore, campaigns (posters) should be able to activate the viewers’ contemplation on such issues. The emergence of multimodal texts provides a vast opportunity for semioticians to do their analyses in a more creative manner in current communication processes. Accordingly, this study focuses on the interactive meanings of semiotic resources in posters on environmental campaigns using a multimodal perspective. It examines the contribution of visual and textual resources to raise people’s awareness on the significance of preserving the environment for future generations. This study drew upon analytical tools from SFL, social semiotics, and reading images (Bezemer Kress, 2008; Kress, 2011; Kress Van Leeuwen 1996; Martinec Salway, 2005). This form of contemplation can be considered to be a part of an essential educational process to build a good character. This study shows that the sample posters are significant to represent and transfer environmental messages through these multimodal resources.